PENGARUH BAHAN PEREKAT DAN WAKTU REDUKSI PADA PEMBUATAN BRIKET SPONGE DARI BIJIH BESI LOKAL[Effect of Binder and Reduction Time in The Preparation of Sponge Iron Briquette from Local Iron Ore] - Jamali, Adil; Mufakhir, Fiqa Rofiq; Amin, Muhammad (Jurnal Metalurgi, 2012)
EFFECT OF BINDER AND REDUCTION TIME IN THE PREPARATION OF SPONGE IRON BRIQUETTE FROM LOCAL IRON ORE. Sponge Iron is an intermediate product in Iron and Steel production through Direct Reduction process of iron ore. In this experiment, sponge iron was made from local iron ore as feed for big Industry and small one that use cupola furnace. The method used was laboratory experiment to find optimum process condition on sponge Iron briquette preparation. From experiment at 1150 ° C , reduction time 40 minutes using bentonite as binder, the optimum sponge metalization of 96 % was obtained. Sponge briquette with starch binder has a slightly better metalization compared to sponge with bentonite binder. Namely 84.26 % and 83.59 % respectively at 60 minutes redution time. The densities are 4.87 g/cm3 and 3.37 g/cm3 respectively. Although starch binded sponge contain less impurities, it is more brittle than bentonite binded sponge. Bentonite binded sponge which has a melting point of 1522 ° C was melted in induction furnace at 1541°C. It is predicted that melting at these temperature using cupola furnace will require a hot blast instead of cold blast cupola. The relatively low reduction temperature of 1150 °C used in the experiment was chosen so that reduction equipment was easy to build and operated. The prospect of the experimental results is that bentonite binded sponge would be suitable as feed of cupola melting furnace due to its better crushing strength. Starch binded sponge is suitable for induction furnace feed , due to its small impurities that will produce a minimum slag. The britle and easily disintegrated starch binded sponge when pulvuriced to powder can be used in waste water treatment.